2020
DOI: 10.1177/1468796820932583
|View full text |Cite
|
Sign up to set email alerts
|

Caring for elderly parents: Perceived filial obligations among Maghrebine immigrants in Italy

Abstract: The migrant population in Southern European countries is aging. In the next future, long-term care needs of immigrant individuals will be a major issue in the evolution of social policies in these countries. In this context, it becomes important to examine what are the norms of filial obligations that govern the exchange of social support within migrant families. The study focuses on solidarity norms and support expectations among Mahgrebine immigrants living in Italy. It is shown that: i. intergenerational co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
6
0
3
Order By: Relevance
“…For instance, a sense of filial duty and moral obligation to care might be greater when migrants' parents live in countries where there is less public health and community services to support older people (Ho & Chiang, 2017). In other words, the cultural meanings of caregiving are mutually constructed with a social context' institutional conditions and welfare provision (Albertini & Semprebon, 2020).…”
Section: Transnational Emotional Care Of Ageing Parents: Conceptual T...mentioning
confidence: 99%
“…For instance, a sense of filial duty and moral obligation to care might be greater when migrants' parents live in countries where there is less public health and community services to support older people (Ho & Chiang, 2017). In other words, the cultural meanings of caregiving are mutually constructed with a social context' institutional conditions and welfare provision (Albertini & Semprebon, 2020).…”
Section: Transnational Emotional Care Of Ageing Parents: Conceptual T...mentioning
confidence: 99%
“…Ello explicaría por qué, por ejemplo, la mayoría de sus encuestados señalaron que la mejor situación para cuidar era que la madre viajara a Italia para ser atendida por alguno de sus hijos. Los autores concluyen que los sistemas con Estados de bienestar menos desarrollados tienden a mantener modelos más familísticos de cuidado, mientras que sociedades con sistemas de bienestar más fuertes tienden a transitar hacia sistemas más individualistas (Albertini y Semprebon, 2020).…”
Section: Una Aproximación Desde La Teoría De Los Cuidados a La Relaci...unclassified
“…Batthyany, Asesina y Brunet (2007) se preguntan para el caso de Uruguay acerca de cómo los cuidados se distribuyen entre el Estado, el mercado y la familia. Esta tríada está a la base de la definición del sistema familístico (Setién y Acosta, 2010) y de los arreglos formales e informales (Albertini y Semprebon, 2020). La mayor o menor presencia de un Estado de bienestar determinaría el mayor o menor involucramiento de las familias.…”
Section: Una Aproximación Desde La Teoría De Los Cuidados a La Relaci...unclassified
“…Among studies that address immigrants’ values of caregiving, individual beliefs about the importance of the family are a central aspect (Albertini and Semprebon 2020 ; Cheung et al 2020 ; Kobayashi and Funk 2010 ; Merz et al 2009 ; Sharma et al 2012 ). In addition, the economic literature has shown that the importance of the family varies across cultures and plays an important role in the value formation of individuals.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A transmission process of cultural traits is not only visible for Asian immigrants who migrate to Western countries, but also for other non-Western immigrants. Albertini and Semprebon ( 2020 ) study filial obligations among Mahgrebine immigrants in Italy. The majority of participants regards co-residence as the best solution to cope with the care needs of a lone older frail mother.…”
Section: Introductionmentioning
confidence: 99%